Environmental Sex Determination in the Branchiopod Crustacean Daphnia magna: Deep Conservation of a Doublesex Gene in the Sex-Determining Pathway - Kato, Yasuhiko (Public Library of Science, 2011)
Sex-determining mechanisms are diverse among animal lineages and can be broadly divided into two major categories: genetic and environmental. In contrast to genetic sex determination (GSD), little is known about the molecular mechanisms underlying environmental sex determination (ESD). The Doublesex (Dsx) genes play an important role in controlling sexual dimorphism in genetic sex-determining organisms such as nematodes, insects, and vertebrates. Here we report the identification of two Dsx genes from Daphnia magna, a freshwater branchiopod crustacean that parthenogenetically produces males in response to environmental cues. One of these genes, designated DapmaDsx1, is responsible for the male trait development when expressed during environmental sex determination. The domain organization of DapmaDsx1 was similar to that of Dsx from insects, which are thought to be the sister group of branchiopod crustaceans. Intriguingly, the molecular basis for sexually dimorphic expression of DapmaDsx1 is different from that of insects. Rather than being regulated sex-specifically at the level of pre–mRNA splicing in the coding region, DapmaDsx1 exhibits sexually dimorphic differences in the abundance of its transcripts. During embryogenesis, expression of DapmaDsx1 was increased only in males and its transcripts were primarily detected in male-specific structures. Knock-down of DapmaDsx1 in male embryos resulted in the production of female traits including ovarian maturation, whereas ectopic expression of DapmaDsx1 in female embryos resulted in the development of male-like phenotypes. Expression patterns of another D. magna Dsx gene, DapmaDsx2, were similar to those of DapmaDsx1, but silencing and overexpression of this gene did not induce any clear phenotypic changes. These results establish DapmaDsx1 as a key regulator of the male phenotype. Our findings reveal how ESD is implemented by selective expression of a fundamental genetic component that is functionally conserved in animals using GSD. We infer that there is an ancient, previously unidentified link between genetic and environmental sex determination.